VIDEO SURVEILLANCE SYSTEMS: STATUS, PROBLEMS AND HARDWARE OF IMAGE PROCESSING - R. Kh. Sadykhov; S. A. Kuchuk (Informatika)
Video systems for surveillance of medium and large objects and these systems hardware (street IP-cameras, servers, data storage devices, operator devices) are surveyed. The issues of image processing, surveillance systems development tendencies and tasks requiring solution are covered.